Implementasi Contextual Teaching and Learning Pada Pembelajaran Aswaja - M Tarwi; Farida Ulfi Naimah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2022)
This article aims to describe the implementation of the Contextual Teaching and Learning (CTL) approach in class VIII Aswaja learning at MTs Miftahul Huda Semanding Tuban. This article uses a case study approach, and is a type of qualitative research. Methods of data collection using interviews, observation, and documentation. Data analysis used the Mathew Miles and A Michael Hubermen model, namely data reduction in presenting data and drawing conclusions (verification). The results of the research from the implementation of CTL in Aswaja Subjects are quite good starting from the preparation of lesson plans, implementation which includes a) learning according to the reasonableness of students' mental development b) forming study groups c) providing an environment that supports independent learning d) considering the diversity of students e) paying attention to multi-intelligence students f) using questioning techniques and g) applying authentic assessment, and the obstacles in this approach 1) The proportionality of educational linearity is not appropriate 2) lack of teaching hours, lack of Aswaja teachers 3) developing learning media namely IT (electronic) media 4 ) The Covid-19 pandemic and 5) the public's view of the administrators working at Muhammadiyah while the impact of the CTL approach 1) high student enthusiasm 2) students can think critically 3) providing adequate learning media.